Microalgae for Aquaculture: The Current Global Situation and Future Trends - Arnaud Muller-Feuga (John Wiley & Sons, Ltd., 2025)
Aquaculture plays a crucial and rapidly increasing role in supplying human foodstuff, with a contribution close to exceeding that of fisheries (some 80 million tons in 2010). Though not harvested, the man-made microalgae production on the basis of freshwater plankton-feeding fish (50% of total aquaculture production) was much higher than total aquaculture and of the order of potatoes or fresh vegetables. Filtering mollusks consuming natural phytoplankton represented 18% of total aquaculture production. With seaweeds, these animal productions are fully sustainable as they are based on renewable resources, providing 85% trophic independence to aquaculture. The remaining productions of crustaceans and fish are fed on agricultural and fisheries products, even if early stages, and even broodstocks are fed on cultivated microalgae. In the context of growing shortage, humanity must increase its supply of food and fuel by extending the primary production to areas highly impacted by sunlight. Especially, the exploitation of water bodies should be intensified as they constitute the largest reserve. Their contribution to primary production could be substantially increased by means of open sea microalgae farms. A concept adapted to this purpose is presented that will confer to aquaculture a major role in human essential supplies in full trophic independence.